United States Economic Interest in the Middle East and the Resolution of the Israeli-Palestinian Conflict - Otu, Eugene Chukwu (EBSU Journal of Social Sciences and Humanities, 2022)
This study interrogates United States Economic Interest in the Middle East and the Resolution of the Israeli-Palestinian Conflict. The aim of the study is to find out United States Interest in the Middle East States and its effect on the Resolution of the Israeli Palestinian Conflict. The researcher adopted intractable conflict theory for the explanation of Israeli-Palestinian conflict. The researcher adopted qualitative research methodology which involves the use of secondary data. The researcher made the following findings, that the Economic interest of United States of America in the Middle East is oil. With the relationship existing between United States and Israel especially in the area of security, they want Israel’s head to remain high in the Middle East which will give them smooth ride in achieving their economic growth. The researcher recommended that United States of America should stay away from Middle East Politics if they can’t play neutral role, United Nations and other relevant international organisations should help curtail the military alliance between United States of America and Israel.